Les enjeux et les déclinaisons de la notion de « santé sexuelle et reproductive » au Maroc. Réflexions à partir du cas des grossesses hors mariage - Irene Capelli (L’Année du Maghreb)
In Morocco, pregnancies and births outside marriage are the subject of many initiatives, especially in the field of non-governmental organizations. Many of these call for changes in family law to ensure that children born out of wedlock are not discriminated against and fight against the social marginalization of single mothers. They provide them with the medical assistance they need and offer them health education activities, also in the area of ​​sexual and reproductive health. The field research I conducted in 2011 and 2012 in hospitals, health centers, NGOs and with women who gave birth outside marriage in Casablanca pushed me to question the stakes of the concept sexual and reproductive health (SRH), its applications and its appropriation by local actors. Beyond information on contraception and illegal abortions, educational activities promoted by local NGOs aimed at young unmarried women aim to prevent "recidivism" and to "empower" the beneficiaries. their services. The trajectories of single mothers reveal a great vulnerability in which socio-economic, gender and health dimensions are interlinked that are not always taken into account by local NGOs. Are discourses, policies and practices inspired by the concept of SRH in Morocco declining in terms of rights or do they produce new forms of normalization and governance of women's bodies? The concept of SRH is sometimes inadequate to capture the complexity of local realities and the subjective experiences of single mothers. The role of broader socio-economic inequalities, moral negotiations and the creation of "target" categories of "vulnerable" beneficiaries within non-governmental organizations rather emerge as elements to be problematized in a critical anthropology of health and reproduction in Morocco.